Elite persistence in Sierra Leone: What can names tell us? - Yannick Dupraz; Rebecca Simson (African Economic History Network (AEHN), 2023)
Can name analysis be used to study elite persistence in African contexts? Taking Sierra Leone as a case study, we use surnames to measure how two historical elites (descendants of settlers that comprise Sierra Leone's Krio community and members of Chiefly Ruling Houses) have fared over the postcolonial period. We find strong and persistent overrepresentation of these groups across a range of postcolonial elites, although decolonisation is associated with a marked decline in political elite persistence. The results also show strong elite compartmentalisation: Chiefly name-holders are more overrepresented in politics and mining, and their overrepresentation falls the more educationally-selective the profession. The Krio, conversely, are increasingly overrepresented the more educationallyselective the sector, and their role in politics diminished rapidly after independence. This speaks to the enduring legacy of the colony-protectorate divide in Sierra Leone, and to different strategies of elite perpetuation, whether through educational investments or political capital. It demonstrates that name-based methods can bring new perspectives to African elite studies.
Keywords: 330; Elite; Soziale Mobilität; Postkolonialismus; Sierra Leone